Determinación de la Degradación Térmica de Polímeros por Análisis de Cambio de Color - Rojas González, Andrés Felipe; Osswald, Tim Andreas (Ingeniería, 2016)
Context: It has been observed that thermal degradation of thermoplastic polymers, when they are reprocessed by injection, extrusion and extrusion / injection, undergo color changes in the product, although it not has been established as this change occurs. Method: It analyzed the effect on thermal degradation caused by polymer type, processing type, polymer grade, rotation speed of the extrusion screw and number of reprocessing, which is quantified by the color change using an empirical equation, with experimental data obtained by analysis through a microcolor colorimeter. Results: It was found that the color change analysis provides information about progress of the thermal degradation and stability of thermoplastic polymers, which are undergoing to multiple reprocessing events and processes. Conclusions: It was established that this technique can be implemented as a simple and efficient measure of thermoplastic products quality control, according to their color change.